Understanding the rapid evaluation of innovative ideas in the early stages of design. (2nd August 2010) - Ferioli, Marcelo; Dekoninck, Elies; Culley, Steve; Roussel, Benoit, Jean Renaud
This paper presents a study that analyses the activity of creative idea evaluation in the early stages of the New Product Development (NPD) process. The focus of this study is on the first evaluation of ideas carried out just after the idea generation phase, which means the very rapid preliminary screening of ideas, normally done by experts. This work was undertaken by analysing in detail the activities of professional design experts who evaluate creative design ideas or concepts in a company. The study shows that there are two distinct stages in their evaluation. The first one is based on the underlying judgement, effectively a technical feasibility filter, using criteria of quite an objective nature. The second one is based upon Subjective Criteria (SC) and interestingly on just a basic 'feeling' or instinct. The research also shows that generally experts spend more time with ideas that will be accepted than ones that will end up rejected. In addition the study indicates that long idea-evaluation sessions are not very beneficial. The data shows a distinct difference in the mindset of the participants after an hour and many more ideas were rejected. This research suggests that good ideas may have been excluded or lost due to the duration of the session.